1994
DOI: 10.1002/app.1994.070541112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of LDPE/granular starch composites

Abstract: SYNOPSISThe mechanical properties of composites of granular starch and low density polyethylene (PE) have been studied as functions of starch volume fraction 4, granule size, and presence of compatibilizer. Property-volume fraction relationships were interpreted using various theories of composite properties. The dependence of elongation (t -41/3) and tensile strength ( IJ -@I3) agree with theoretical predictions, although the proportionality constants are less negative than theoretical values. The addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
140
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(154 citation statements)
references
References 29 publications
12
140
0
2
Order By: Relevance
“…At constant filler content, modulus, tensile stress, and yield stress decrease with increase in particle size. Nonetheless, Willett (1994) noted that adhesion played a greater role than particle size on starch-polyethylene composite tensile strength. On the other hand, Nielsen (1974) earlier opined that good adhesion was not that important provided the frictional forces between the phases were not surpassed by the applied external stresses.…”
Section: Starch As Fillersmentioning
confidence: 99%
“…At constant filler content, modulus, tensile stress, and yield stress decrease with increase in particle size. Nonetheless, Willett (1994) noted that adhesion played a greater role than particle size on starch-polyethylene composite tensile strength. On the other hand, Nielsen (1974) earlier opined that good adhesion was not that important provided the frictional forces between the phases were not surpassed by the applied external stresses.…”
Section: Starch As Fillersmentioning
confidence: 99%
“…As shown in Table 3, the addition of MDI/PMMA-modified starch consistently increased the torque values of SBR compounds, including M L , M H and Delta M. Two reasons may be responsible as below. First, as reported in the literature, 31 the Young's modulus of starch was approximately 15 GPa, which was much higher than that of raw SBR (< 10 MPa). The addition of starch restricted the movement of SBR macromolecular chains and therefore increased the torque values of SBR compounds.…”
Section: Effect Of Starch Concentration On the Performances Of Mdi/pmmentioning
confidence: 66%
“…For corn starch, the E f was estimated to be approximately 15 GPa. 31 The comparison between the experimentally measured 300% modulus and theoretically predicted modulus using Guth-Gold model, Modified Guth-Gold model and Halpin-Tsai model are shown in Figure 6. It is observed that the theoretically predicted values using the Guth-Gold model were much lower than the experimentally measured values, since the formation of some extent of complex networks from starch agglomerates can't be neglected.…”
Section: Effect Of Starch Concentration On the Performances Of Mdi/pmmentioning
confidence: 99%
“…Figure 6a shows that the reduction of the glycerol content from 40% to 33% results in a quasi-linear increment of G', while the reduction from 33% to 29% glycerol produces a larger variation in G'. In the case of the elastic modulus of polymer composites, percolation theory explains the non-linearity produced by the phase inversion effect at high filler content (Willett, 1994). The limit of glycerol plasticization that produces the non-linearity observed in the G' of TPS at a concentration around 30% glycerol can be explained in a similar way.…”
Section: Rheological and Thermal Properties Of Water-free Tpsmentioning
confidence: 94%
“…It has be used in its native granular form as rigid filler or transformed in a thermoplastic material for melt blending with synthetic or natural polymers. Polymers filled with dry starch granules behave as typical composite materials where modulus increases and ductility decreases due to the stiffening effect of the starch granules (Willett, 1994, Kim et al, 1995, Chandra & Rustgi, 1997). An important disadvantage showed by polymeric composites filled with granular starch is the low starch content that can be added, especially for application where high ductility is required (Griffith, 1977).…”
Section: Introductionmentioning
confidence: 99%